A Diagnostic Overview of Geriatric Oral Cavity in Randegansari, Gresik - Nurfitri Amaliah; Danella Yustiono; R. P. Arief Rakhman (AMK : Abdi Masyarakat UIKA, 2026)
As the global population ages, the intersection of systemic health, polypharmacy, and oral pathology presents a growing challenge for geriatric care. In elderly populations, oral health is often a reflection of systemic well-being, where chronic diseases and their pharmacological treatments directly modify the oral environment. This study aimed to provide a diagnostic overview of the oral health status—specifically dental caries experience and oral mucosal lesions—among a geriatric and pre-geriatric cohort in Randegansari, Gresik. A descriptive cross-sectional study was conducted involving 35 respondents (62.9% female; 37.1% male). Clinical examinations were performed to determine the Decayed, Missing, and Filled Teeth (DMF-T) index and to identify Oral Mucosal Lesions (OMLs). Systemic health history and routine medication use were also recorded to contextualize clinical findings. The mean DMF-T score for the population was 6.86, categorized as "Very High" according to WHO severity scales. The index was dominated by the Decayed (4.29) and Missing (2.51) components, while the Filling component was remarkably low (0.06). Systemic comorbidities were prevalent, with Diabetes Mellitus (34.3%) and Hypertension (25.7%) being the most frequent, accompanied by high rates of polypharmacy (71.4%). Notably, 100% of respondents exhibited oral mucosal findings, with Coated Tongue being the most ubiquitous lesion across all age and gender groups. There is an urgent need for integrated geriatric health programs that prioritize biofilm control, tongue hygiene, and minimally invasive restorative interventions to prevent further dental loss.